Spending Behavior of Public School Teachers: Implementation of Financial Wellness Program - Cabaroc, Ma. Dhanna Luisa (Journal of Interdisciplinary Perspectives, 2025)
This descriptive study assessed the spending behavior of public school teachers in District II, Quezon City, alongside their socio-economic profiles and the potential benefits of a financial wellness program. The study involved 298 secondary public school teachers, selected using stratified random sampling to ensure proportional representation across district schools. The selection process accounted for school size and the number of teachers per school relative to the total district population. Data was collected through a structured survey to capture detailed socioeconomic information and spending behaviors. The findings revealed that most respondents had 1 to 2 dependents, full-time employed spouses, and a gross monthly income of 20,000–40,000 pesos. A majority relied solely on their teaching income without additional sources. Significant differences were observed between socio-economic profiles and spending behaviors. Key contributing factors included regular saving patterns, debt management, financial decisions, and financial planning. The study recommends implementing financial education programs focusing on budgeting, saving, debt management, retirement planning, and investment to address these issues. Promoting peer support networks and responsible financial products is also essential to enhance financial wellness.